No Overactivism: Robert Lewandowski’s Use of Gentle Protest to Avoid National Political Backlash - Bridgman, Timothy (International Studies. Interdisciplinary Political and Cultural Journal, 2024)
The last few years have seen the return of athlete activism into major international sports events held worldwide as a mindset based on social responsibility and political freedom of speech has spread into the selfperception of many current top athletes. However, while these athletes may have experienced a recent personal transformation, the national political backlash accompanying activism remains set in a long tradition condemning political interference in sports. This article provides a background on the tradition of castigating political athlete activists, a theory on why and how national political backlash occurs, and evidence on the successful use of gentle activism to avoid such scenarios. The research examines a case study of Polish international footballer Robert Lewandowski’s ‘pointing the finger’ during a World Cup qualifier in 2022 to illustrate how alternative moderate forms of activism can be adopted. This study aims to introduce the term ‘overactivism’ into the politics of sport as a concept where the athlete prioritises retaining long-term political relevancy over maximising the political impact of a single event.